Making Progress Towards »Green« Propellants – Part II. Issue 8 (26th May 2020) - Dejeaifve, Alain; Sarbach, Alexandre; Roduit, Bertrand; Folly, Patrick; Dobson, Rowan
Abstract: Nitrate‐ester based propellants require stabilisers in order to maintain good chemical stability and to prevent oxidation, chain scission, energy loss and uncontrolled heat generation that are caused by homolytic and heterolytic cleavage of the weakest nitrogen‐oxygen bond of the nitrate ester functional group. With REACH legislation (1907/2006), industry in Europe has made progress in using less toxic compounds, that are often more environmentally‐friendly. This work aims to go beyond REACH and to anticipate the inclusion of other molecules that produce non‐ or less toxic daughter products and that can fulfil their role in the propellant's formulation. This paper is the follow‐up to a first paper, presenting six families of "green" stabilisers, which are novel, environmentally friendly, efficient and readily available for use in nitrocellulose‐based compositions. In this article we present the validated lower temperature shelf life predictions for propellants containing the new stabilisers, using heat flow calorimetry (HFC). It will be necessary to modify AOP48 in the near future to be able to include these new stabilisers that provide much better performances than conventional ones (longer shelf lives of propellants) and are also respectful of the environment and human health. Abstract :